"It all comes down to the leadership": The role of the school principal in fostering parent-school engagement. (July 2014) - Barr, Jenny; Saltmarsh, Sue
Parent-school engagement is widely understood to be an important factor in children's school experience and educational outcomes. However, there is considerable variation in the ways that schools manage their relationships with parents, as well as variation in what parents themselves view as important for engagement with their children's schooling. In a qualitative study conducted with parents in urban, outer metropolitan, regional and rural areas of the Australian state of New South Wales, we found that parents considered the attitudes, communication and leadership practices of school principals to play a crucial role in fostering and maintaining relationships between parents and schools. These findings suggest that despite policy rhetorics positioning schools and parents as 'partners' in the educational equation, parents are more likely to be engaged with schools where the principal is perceived as welcoming and supportive of their involvement, and less likely to be engaged where the principal is perceived as inaccessible, dismissive or disinterested in supporting their involvement.